Positive electrode for secondary battery and secondary battery
Patent Information
- Application Number
- JP2023128330
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-07
- Publication Date
- 2025-02-20
- Estimated Expiration
- 2043-08-07
AI Technical Summary
【0009】 本技術の一実施形態の二次電池用正極または二次電池によれば、正極活物質層が正極活物質および正極結着剤を含み、その正極活物質がオリビン型の結晶構造を有するリン酸化合物を含み、その正極結着剤が水溶性高分子化合物および脂溶性高分子化合物を含み、その正極活物質層における水溶性高分子化合物の含有量が1重量%以上2重量%以下であり、その正極活物質層における脂溶性高分子化合物の含有量が2重量%以上6重量%以下であるので、優れた電池特性を得ることができる。
Smart Images

Figure 2025024308000001_ABST
Abstract
Description
[Technical field]
[0001] The present technology relates to a positive electrode for a secondary battery and a secondary battery. [Background technology]
[0002] Due to the widespread use of various electronic devices such as mobile phones, secondary batteries have been developed as power sources that are small and lightweight and can provide high energy density. These secondary batteries include a positive electrode, which is the positive electrode for the secondary battery, as well as a negative electrode and an electrolyte, and various studies have been conducted on the configuration of the secondary battery.
[0003] Specifically, the positive electrode active material contains olivine-type lithium phosphate, and the binder contains polyacrylonitrile (see, for example, Patent Document 1). Also, the positive electrode active material contains a lithium composite oxide having an olivine structure, and the binder contains an acrylonitrile-based copolymer (see, for example, Patent Document 2). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2005-251554 A [Patent Document 2] JP 2010-272272 A Summary of the Invention [Problem to be solved by the invention]
[0005] Although various studies have been conducted on the configuration of secondary batteries, the battery characteristics of the secondary batteries are still insufficient and there is room for improvement.
[0006] There is a demand for a positive electrode for a secondary battery and a secondary battery that are capable of obtaining excellent battery characteristics. [Means for solving the problem]
[0007] A positive electrode for a secondary battery according to an embodiment of the present technology includes a positive electrode active material layer, the positive electrode active material layer including a positive electrode active material and a positive electrode binder. The positive electrode active material includes a phosphoric acid compound having an olivine crystal structure. The positive electrode binder includes a water-soluble polymer compound and an oil-soluble polymer compound, the water-soluble polymer compound includes at least one polymer selected from acrylates, acrylonitrile, and acrylamide, and the oil-soluble polymer compound includes at least one polymer selected from acrylonitrile, acrylic acid esters, and methacrylic acid esters. The content of the water-soluble polymer compound in the positive electrode active material layer is 1% by weight or more and 2% by weight or less, and the content of the oil-soluble polymer compound in the positive electrode active material layer is 2% by weight or more and 6% by weight or less.
[0008] A secondary battery according to an embodiment of the present technology includes a positive electrode, a negative electrode, and an electrolyte, and the positive electrode has a configuration similar to that of the positive electrode for a secondary battery according to the embodiment of the present technology described above. Effect of the Invention
[0009] According to the positive electrode for secondary batteries or the secondary battery of one embodiment of the present technology, the positive electrode active material layer contains a positive electrode active material and a positive electrode binder, the positive electrode active material contains a phosphate compound having an olivine crystal structure, the positive electrode binder contains a water soluble polymer compound and an oil soluble polymer compound, the content of the water soluble polymer compound in the positive electrode active material layer is 1 wt % or more and 2 wt % or less, and the content of the oil soluble polymer compound in the positive electrode active material layer is 2 wt % or more and 6 wt % or less, so that excellent battery characteristics can be obtained.
[0010] Note that the effects of the present technology are not necessarily limited to the effects described here, but may be any of a series of effects related to the present technology described below. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a cross-sectional view illustrating a configuration of a positive electrode for a secondary battery in one embodiment of the present technology. [Diagram 2]FIG. 2 is a cross-sectional view illustrating a configuration of a secondary battery according to an embodiment of the present technology. [Diagram 3] FIG. 3 is a cross-sectional view illustrating the configuration of the battery element shown in FIG. [Figure 4] FIG. 4 is a cross-sectional view showing the configuration of a test secondary battery. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, an embodiment of the present technology will be described in detail with reference to the drawings. The description will be given in the following order. 1. Positive electrodes for secondary batteries 1-1.Configuration 1-2.Operation 1-3. Manufacturing method 1-4. Actions and Effects 2. Secondary battery 2-1.Configuration 2-2.Operation 2-3. Manufacturing method 2-4. Actions and Effects 3. Variations 4. Uses of secondary batteries
[0013] <1. Positive electrodes for secondary batteries> First, a positive electrode for a secondary battery (hereinafter simply referred to as a "positive electrode") according to an embodiment of the present technology will be described.
[0014] The positive electrode described here is used in a secondary battery, which is an electrochemical device. However, the positive electrode may be used in electrochemical devices other than secondary batteries. Specific examples of other electrochemical devices include primary batteries and capacitors.
[0015] The positive electrode absorbs and releases an electrode reactant during the operation of the electrochemical device, i.e., during the electrode reaction. The type of the electrode reactant is not particularly limited, but specifically, it is a light metal such as an alkali metal or an alkaline earth metal. Specific examples of the alkali metal include lithium, sodium, and potassium, and specific examples of the alkaline earth metal include beryllium, magnesium, and calcium.
[0016] In the following, an example will be given in which the electrode reactant is lithium, whereby lithium is absorbed and released in an ionic state in the positive electrode during the electrode reaction.
[0017] <1-1. Configuration> 1 shows a cross-sectional configuration of a positive electrode 100, which is an example of a positive electrode according to an embodiment of the present technology. As shown in FIG. 1, the positive electrode 100 includes a positive electrode active material layer 100B.
[0018] Here, the positive electrode 100 further includes a positive electrode current collector 100A that supports the positive electrode active material layer 100B. However, the positive electrode current collector 100A may be omitted.
[0019] [Positive electrode current collector] The positive electrode current collector 100A is a conductive member that supports the positive electrode active material layer 100B, and has a pair of surfaces on which the positive electrode active material layer 100B is provided. The positive electrode current collector 100A contains a conductive material such as a metal material, and a specific example of the conductive material is aluminum.
[0020] [Cathode active material layer] Here, the positive electrode active material layer 100B is provided on one surface of the positive electrode current collector 100A. However, the positive electrode active material layer 100B may be provided on both surfaces of the positive electrode current collector 100A.
[0021] The positive electrode active material layer 100B contains a positive electrode active material and a positive electrode binder, but may further contain one or more of other materials such as a positive electrode conductive agent.
[0022] (Cathode active material) The positive electrode active material contains a plurality of particulate substances (hereinafter referred to as "a plurality of positive electrode active material particles") that absorb and release lithium, and the positive electrode active material particles contain one or more types of phosphate compounds having an olivine crystal structure. Hereinafter, the phosphate compound having an olivine crystal structure is referred to as an "olivine type phosphate compound."
[0023] The reason why the positive electrode active material particles contain an olivine-type phosphate compound is that the crystal structure of the olivine-type phosphate compound is strong and stable, and thus oxygen is prevented from being released from the olivine-type phosphate compound during the electrode reaction of the positive electrode 100. This allows lithium to be stably absorbed and released in the positive electrode active material layer 100B, and the electrode reaction proceeds stably. As a result, a secondary battery including the positive electrode 100 can obtain a stable battery capacity and improve the safety of the secondary battery.
[0024] Here, as described above, since the electrode reactant is lithium, the olivine-type phosphate compound contains lithium, phosphorus, and oxygen as constituent elements. In this case, the type of the olivine-type phosphate compound is not particularly limited as long as it contains lithium, phosphorus, and oxygen as constituent elements.
[0025] The olivine-type phosphate compound may further contain one or more of metal elements other than lithium as a constituent element. The type of metal element is not particularly limited, but specific examples include iron, manganese, cobalt, nickel, titanium, chromium, vanadium, zinc, tin, tungsten, zirconium, magnesium, and aluminum.
[0026] Among them, the metal element preferably contains one or both of iron and manganese. That is, the olivine-type phosphate compound preferably contains one or both of iron and manganese as a constituent element. This is because the release of oxygen from the olivine-type phosphate compound is sufficiently suppressed.
[0027] More specifically, the olivine-type phosphate compound preferably contains one or more of the compounds represented by formula (1). When the olivine-type phosphate compound contains two or more metal elements (Me) as constituent elements, the mixing ratio (molar ratio) of the two or more metal elements can be set arbitrarily.
[0028] Li x MePO 4 (1) (Me is at least one of Fe, Mn, Co, Ni, Ti, Cr, V, Zn, Sn, W, Zr, Mg, and Al. x satisfies 0.9≦x≦1.1.)
[0029] A specific example of an olivine-type phosphate compound is LiFePO 4 , LiMnPO 4 , Life 0.5 Mn 0.5 PO 4 and Life 0.5 Co 0.5 PO 4 And so on.
[0030] Here, since the positive electrode active material particles are secondary particles, the positive electrode active material preferably contains a plurality of positive electrode active material particles, which are a plurality of secondary particles. In addition, since the secondary particles contain a plurality of primary particles, it is preferable that the secondary particles are an aggregate of the plurality of primary particles. This is because the conductivity of the positive electrode active material layer 100B is improved.
[0031] In particular, the olivine-type phosphate compound has inherently low electronic conductivity. Therefore, in order to improve the electrical conductivity of the olivine-type phosphate compound, it is preferable that the olivine-type phosphate compound has a structure of a plurality of fine particles. Therefore, it is preferable to configure the positive electrode active material particles so that they become secondary particles that are an aggregate of a plurality of primary particles by granulating the positive electrode active material particles.
[0032] This allows the secondary particles to easily contact each other, improving the electronic conductivity between the secondary particles, and allows the primary particles to easily contact each other, improving the electronic conductivity between the primary particles. As a result, the electrical conductivity within the positive electrode active material particles is improved, and the electrical conductivity between the positive electrode active material particles is also improved, improving the electrical conductivity of the positive electrode active material layer 100B.
[0033] The median diameter MD2 of the positive electrode active material particles, which are the secondary particles, is not particularly limited, but is preferably 5 μm to 15 μm in particular, because the secondary particles are more likely to come into contact with each other, and thus the electronic conductivity between the secondary particles is further improved.
[0034] Here, the secondary particles are formed by agglomeration of the primary particles. The median diameter MD1 of the primary particles is not particularly limited, but is preferably 0.1 μm to 1 μm. This is because the primary particles are more likely to come into contact with each other, and thus the electronic conductivity between the primary particles is improved.
[0035] The procedure for measuring the median diameter MD2 is as follows. Here, a case where the positive electrode active material layer 100B contains a plurality of positive electrode active material particles, a positive electrode binder, and a positive electrode conductive agent will be described.
[0036] In order to measure the median diameter MD2, a plurality of positive electrode active material particles are analyzed using a particle size measuring device, such as the LA-960 laser diffraction / scattering particle size distribution measuring device manufactured by Horiba, Ltd.
[0037] More specifically, when measuring the median diameter MD2, first, the positive electrode 100 is put into an aqueous solvent, and then the aqueous solvent is stirred to peel off the positive electrode active material layer 100B from the positive electrode current collector 100A. The type of aqueous solvent is not particularly limited, but specifically, it is pure water that can dissolve the positive electrode binder. The details of the aqueous solvent described here are the same hereinafter.
[0038] Next, the positive electrode active material layer 100B is put into an aqueous solvent, the aqueous solvent is stirred, and then the aqueous solvent is filtered, whereby the water-soluble polymer compound in the positive electrode binder is dissolved and removed, and the multiple positive electrode active material particles, the fat-soluble polymer compound, and the positive electrode conductive agent, which are solid contents, are recovered.
[0039] Next, the solid content is put into the aqueous solvent, and then the solid content in the aqueous solvent is centrifuged using a centrifuge. As a result, the plurality of positive electrode active material particles are separated from the fat-soluble polymer compound and the positive electrode conductive agent, and the plurality of positive electrode active material particles are collected. Finally, the median diameter MD2 is measured by analyzing the plurality of positive electrode active material particles using a particle size measuring device.
[0040] The procedure for measuring the median diameter MD1 is as follows. First, a scanning electron microscope (SEM) is used to observe the cross section of the positive electrode active material layer 100B (observation magnification = 10,000 times). As a result, the multiple positive electrode active material particles contained in the positive electrode active material layer 100B are observed, and therefore the multiple primary particles forming each of the multiple positive electrode active material particles (multiple secondary particles) are observed. Next, 50 primary particles whose entire contours (outer edges) can be observed are selected from the multiple primary particles, and the particle diameters of the 50 primary particles are measured. This particle diameter is the diameter of the major axis (the maximum diameter in the direction of the major axis) when the primary particle includes a major axis and a minor axis. Finally, the average value of the particle diameters of the 50 particles is calculated to obtain the median diameter MD1.
[0041] (Positive electrode binder) The positive electrode binder is a material that binds particles such as a plurality of positive electrode active material particles to one another, and contains a water-soluble polymer compound and an oil-soluble polymer compound.
[0042] The water-soluble polymer compound is a polymer compound that can be dissolved in an aqueous solvent such as pure water, and the type of the water-soluble polymer compound may be one kind or two or more kinds.
[0043] Specifically, the water-soluble polymer compound contains one or more polymers of acrylates, acrylonitrile, and acrylamide. That is, the water-soluble polymer compound may be a homopolymer in which one of acrylates, acrylonitrile, and acrylamide is polymerized with itself. The water-soluble polymer compound may also be a copolymer in which two or more of acrylates, acrylonitrile, and acrylamide are polymerized with itself. The acrylonitrile described here is water-soluble, as is clear from the fact that it is a candidate for the water-soluble polymer compound.
[0044] Therefore, the water-soluble polymer compound may be a polyacrylate, a polyacrylonitrile, or a polyacrylamide.The water-soluble polymer compound may be an acrylate-acrylonitrile copolymer, an acrylonitrile-acrylamide copolymer, an acrylate-acrylamide copolymer, or an acrylate-acrylonitrile-acrylamide copolymer.
[0045] The acrylate is a so-called metal acrylate. The type of the acrylate is not particularly limited, but specifically, it is any one or more of metal acrylates such as lithium acrylate, sodium acrylate, and potassium acrylate.
[0046] The content of the water-soluble polymer compound in the positive electrode active material layer 100B is optimized in relation to the content of the fat-soluble polymer compound in the positive electrode active material layer 100B described below, and is specifically 1 to 2% by weight.
[0047] The fat-soluble polymer compound is a polymer compound that is insoluble in an aqueous solvent such as pure water, and the type of the fat-soluble polymer compound may be one type or two or more types. That is, the fat-soluble polymer compound is a polymer compound that is insoluble in an aqueous solvent but is soluble in an organic solvent such as N-methyl-2-pyrrolidone.
[0048] Specifically, the fat-soluble polymer compound contains one or more polymers of acrylonitrile, acrylic acid esters, and methacrylic acid esters. That is, the fat-soluble polymer compound may be a homopolymer, which is a compound in which any one of acrylonitrile, acrylic acid esters, and methacrylic acid esters is polymerized with each other. The fat-soluble polymer compound may also be a copolymer, which is a compound in which any two or more of acrylonitrile, acrylic acid esters, and methacrylic acid esters are polymerized with each other. The acrylonitrile described here is a fat-soluble acrylonitrile, as is clear from the fact that it is a candidate for the fat-soluble polymer compound.
[0049] Therefore, the fat-soluble polymer compound may be polyacrylonitrile, polyacrylic acid ester, or polymethacrylic acid ester. The fat-soluble polymer compound may also be an acrylonitrile-acrylic acid ester copolymer, an acrylic acid ester-methacrylic acid ester copolymer, an acrylonitrile-methacrylic acid ester copolymer, or an acrylonitrile-acrylic acid ester-methacrylic acid ester copolymer.
[0050] The type of acrylic acid ester is not particularly limited, but specifically, it is one or more of methyl acrylate, ethyl acrylate, propyl acrylate, etc. The type of methacrylic acid ester is not particularly limited, but specifically, it is one or more of methyl methacrylate, ethyl methacrylate, propyl methacrylate, etc.
[0051] The content of the fat-soluble polymer compound in the positive electrode active material layer 100B is optimized in relation to the content of the water-soluble polymer compound in the positive electrode active material layer 100B described above, and is specifically 2% to 6% by weight.
[0052] The positive electrode binder contains a water-soluble polymer compound and an oil-soluble polymer compound, and the content of the water-soluble polymer compound in the positive electrode active material layer 100B is 1 wt % to 2 wt %, and the content of the oil-soluble polymer compound in the positive electrode active material layer 100B is 2 wt % to 6 wt %, because this improves the physical durability of the positive electrode 100 and improves the operational stability of a secondary battery including the positive electrode 100.
[0053] In detail, when a water-soluble polymer compound is used as the positive electrode binder, the water-soluble polymer compound functions as a dispersant and a thickener in an aqueous solvent in the manufacturing process of the positive electrode 100 described below, more specifically, in the preparation process of a positive electrode mixture slurry using an aqueous solvent.
[0054] In this case, the dispersibility of the positive electrode active material particles in the aqueous solvent is improved, so that the positive electrode active material particles are uniformly dispersed in the positive electrode mixture slurry, and the viscosity of the positive electrode mixture slurry is stabilized, so that the positive electrode mixture slurry can be stably applied to the surface of the positive electrode current collector 100A.
[0055] As a result, when the positive electrode active material layer 100B is formed using the positive electrode mixture slurry, a small amount of positive electrode binder is used to easily bind the positive electrode active material particles together. In addition, when the positive electrode mixture slurry is applied, the positive electrode active material particles are supplied to the surface of the positive electrode current collector 100A in a uniformly dispersed state. Therefore, the positive electrode active material layer 100B is stably formed, and the operating stability of the secondary battery including the positive electrode 100 is improved.
[0056] In this case, particularly in the step of preparing the positive electrode mixture slurry, an aqueous solvent is used as the solvent instead of an organic solvent, thereby reducing the environmental load.
[0057] However, when a water-soluble polymer compound is used as the positive electrode binder, increasing the thickness of the positive electrode active material layer 100B to increase the energy density of the positive electrode 100 makes the positive electrode active material layer 100B harder. In this case, the flexibility of the positive electrode active material layer 100B decreases, and the adhesion of the positive electrode active material layer 100B to the positive electrode current collector 100A also decreases. This makes the positive electrode active material layer 100B more likely to crack and peel off from the positive electrode current collector 100A.
[0058] Therefore, when an oil-soluble polymer compound is used as the positive electrode binder instead of a water-soluble polymer compound, the positive electrode active material layer 100B is less likely to harden, and therefore the flexibility of the positive electrode active material layer 100B is improved, and the adhesion of the positive electrode active material layer 100B to the positive electrode current collector 100A is also improved. As a result, the positive electrode active material layer 100B is less likely to crack and is less likely to peel off from the positive electrode current collector 100A, and therefore the physical durability of the positive electrode 100 is improved.
[0059] However, as described above, the fat-soluble polymer compound is insoluble in the aqueous solvent. Therefore, in the preparation process of the positive electrode mixture slurry using the aqueous solvent, a water-soluble polymer compound that is soluble in the aqueous solvent can be used, but a fat-soluble polymer compound that is insoluble in the aqueous solvent cannot be used. That is, when the aqueous solvent is used as the solvent for preparing the positive electrode mixture slurry, the water-soluble polymer compound and the fat-soluble polymer compound cannot be used in combination.
[0060] For these reasons, an emulsion solution containing a water-soluble polymer compound and an oil-soluble polymer compound is used as a positive electrode binder in the process of preparing the positive electrode mixture slurry. In this emulsion solution, the water-soluble polymer compound is dissolved in an aqueous solvent, and the oil-soluble polymer compound is dispersed in the aqueous solvent.
[0061] This allows a water-soluble polymer compound and an oil-soluble polymer compound to be used in combination as a positive electrode binder while using an aqueous solvent as a solvent, and therefore a positive electrode mixture slurry containing both a water-soluble polymer compound and an oil-soluble polymer compound is prepared in the positive electrode mixture slurry preparation step.
[0062] In this case, the positive electrode active material layer 100B formed by using the positive electrode mixture slurry contains both a water-soluble polymer compound and an oil-soluble polymer compound as a positive electrode binder. This provides both advantages based on the water-soluble polymer compound and the oil-soluble polymer compound, and as described above, improves the physical durability of the positive electrode 100 and improves the operational stability of a secondary battery including the positive electrode 100.
[0063] In particular, the content of the water-soluble polymer compound in the positive electrode active material layer 100B is preferably 1% by weight to 1.5% by weight, because this further improves the physical durability of the positive electrode 100 and further improves the operational stability of a secondary battery including the positive electrode 100.
[0064] The content of the fat-soluble polymer compound in the positive electrode active material layer 100B is preferably 3% by weight to 5% by weight, because this further improves the physical durability of the positive electrode 100 and further improves the operational stability of a secondary battery including the positive electrode 100.
[0065] Here, the procedure for confirming whether the positive electrode binder contains a water-soluble polymer compound after the fact is as described below. In the following, the case where the positive electrode active material layer 100B contains a plurality of positive electrode active material particles, a positive electrode binder, and a positive electrode conductive agent will be described. Note that the above-mentioned "after the fact" means after the positive electrode 100 is completed.
[0066] First, the positive electrode 100 is placed in an aqueous solvent, and the aqueous solvent is then stirred, whereby the water-soluble polymer compound in the positive electrode binder is dissolved in the aqueous solvent.
[0067] Next, the aqueous solvent is filtered, and the filtrate is collected, whereby the filtrate, which includes the positive electrode current collector 100A, the positive electrode active material particles, the fat-soluble polymer compound, the positive electrode conductive agent, and other solid matters, is removed, and a filtrate containing the water-soluble polymer compound is obtained.
[0068] Finally, the filtrate is analyzed using one or more of the following analytical methods: Fourier transform infrared spectroscopy (FT-IR), pyrolysis gas chromatography mass spectrometry (GC / MS), and solution nuclear magnetic resonance spectroscopy (NMR). This allows the composition of the substances contained in the filtrate to be analyzed, and it is possible to confirm whether the positive electrode binder contains a water-soluble polymer compound or not.
[0069] The procedure for measuring the content of the water-soluble polymer compound in the positive electrode active material layer 100B afterwards is as described below.
[0070] First, the weight of the positive electrode active material layer 100B is measured by peeling the positive electrode current collector 100A from the positive electrode active material layer 100B.
[0071] Next, the positive electrode active material layer 100B is placed in the aqueous solvent, and the aqueous solvent is then stirred, whereby the water-soluble polymer compound in the positive electrode binder is dissolved in the aqueous solvent.
[0072] Next, the aqueous solvent is filtered, and the filtrate is collected, whereby the filtrate, which includes the positive electrode current collector 100A, the positive electrode active material particles, the fat-soluble polymer compound, the positive electrode conductive agent, and other solid matters, is removed, and a filtrate containing the water-soluble polymer compound is obtained.
[0073] The filtrate is then heated. Heating conditions such as heating temperature and heating time can be set as desired. This causes the aqueous solvent to volatilize, and the water-soluble polymer compound, which is a dried product, is then recovered. The weight of the water-soluble polymer compound is then measured.
[0074] Finally, based on the weight of the positive electrode active material layer 100B and the weight of the water-soluble polymer compound, the content of the water-soluble polymer compound in the positive electrode active material layer 100B is calculated based on the formula: content (wt%)=(weight of the water-soluble polymer compound / weight of the positive electrode active material layer 100B)×100.
[0075] In addition, the procedure for confirming after the fact whether the positive electrode binder contains a fat-soluble polymer compound or not is as described below. In the following, a case where the positive electrode active material layer 100B contains a plurality of positive electrode active material particles, a positive electrode binder, and a positive electrode conductive agent will be described.
[0076] First, a filtrate is obtained using the same procedure as in the case of confirming after the fact whether the positive electrode binder contains a water-soluble polymer compound. As described above, this filtrate contains the positive electrode current collector 100A, the positive electrode active material particles, and the positive electrode conductive agent, together with the fat-soluble polymer compound that is insoluble in aqueous solvents.
[0077] Then, the filtrate is put into the organic solvent, and the organic solvent is stirred.The type of the organic solvent is not particularly limited as long as it is an organic solvent that can dissolve the fat-soluble polymer compound, and specifically, it is one or more of organic solvents such as N-methyl-2-pyrrolidone.Thereby, the fat-soluble polymer compound is dissolved in the organic solvent.
[0078] Next, the organic solvent is filtered, and the filtrate is collected, whereby the filtrate, which includes the positive electrode current collector 100A, the positive electrode active material particles, the positive electrode conductive agent, and other solid matters, is removed, and a filtrate containing the fat-soluble polymer compound is obtained.
[0079] Finally, the filtrate is analyzed using one or more of the following analytical methods: Fourier transform infrared spectroscopy (FT-IR), pyrolysis gas chromatography mass spectrometry (GC / MS), and solution nuclear magnetic resonance spectroscopy (NMR). This allows the composition of the substances contained in the filtrate to be analyzed, and therefore it is possible to confirm whether the positive electrode binder contains a fat-soluble polymer compound or not.
[0080] The procedure for measuring the content of the fat-soluble polymer compound in the positive electrode active material layer 100B afterwards is as described below.
[0081] First, the weight of the positive electrode active material layer 100B is measured using a procedure similar to that used in the subsequent measurement of the content of the water-soluble polymer compound in the positive electrode active material layer 100B.
[0082] Next, the positive electrode active material layer 100B is placed in the organic solvent, and the organic solvent is stirred, whereby the fat-soluble polymer compound in the positive electrode binder is dissolved in the organic solvent.
[0083] Next, the organic solvent is filtered, and the filtrate is collected, whereby the filtrate containing the fat-soluble polymer compound is obtained, since the filtrate, which includes the positive electrode current collector 100A, the positive electrode active material particles, the water-soluble polymer compound, the positive electrode conductive agent, and other solid matters, is removed.
[0084] The filtrate is then heated. Heating conditions such as heating temperature and heating time can be set as desired. This causes the organic solvent to volatilize, and the fat-soluble polymer compound, which is a dried product, is then recovered. The weight of the fat-soluble polymer compound is then measured.
[0085] Finally, based on the weight of the positive electrode active material layer 100B and the weight of the fat-soluble polymer compound, the content of the fat-soluble polymer compound in the positive electrode active material layer 100B is calculated based on the formula: content (wt%)=(weight of fat-soluble polymer compound / weight of positive electrode active material layer 100B)×100.
[0086] (Positive electrode conductive agent) The positive electrode conductive agent is a material that improves the conductivity of the positive electrode active material layer 100B, and contains one or more conductive materials such as carbon materials, metal materials, and conductive polymer compounds, etc. Specific examples of carbon materials include graphite, carbon black, acetylene black, and ketjen black.
[0087] <1-2. Operation> In this positive electrode 100, during an electrode reaction, lithium is released in an ionic state from the positive electrode active material layer 100B, and lithium is absorbed in an ionic state in the positive electrode active material layer 100B.
[0088] <1-3. Manufacturing method> The cathode 100 is fabricated using an example procedure described below.
[0089] First, a positive electrode mixture slurry is prepared by mixing a plurality of positive electrode active material particles, an emulsion solution, a positive electrode conductive agent, and a solvent for adjusting viscosity.
[0090] As described above, this emulsion solution is a solution in which a water-soluble polymer compound is dissolved in an aqueous solvent and a fat-soluble polymer compound is dispersed in the aqueous solvent. The type of the viscosity adjusting solvent is not particularly limited, but specifically, it is an aqueous solvent such as pure water.
[0091] In this case, the content of the water-soluble polymer compound in the emulsion solution is adjusted so that the content of the water-soluble polymer compound in the cathode active material layer 100B formed in the later process falls within the above-mentioned range. Also, the content of the fat-soluble polymer compound in the emulsion solution is adjusted so that the content of the fat-soluble polymer compound in the cathode active material layer 100B formed in the later process falls within the above-mentioned range.
[0092] Next, the positive electrode mixture slurry is applied to one surface of the positive electrode current collector 100A to form the positive electrode active material layer 100B.
[0093] Finally, if necessary, the positive electrode active material layer 100B is compression molded using a compression device such as a roll press, etc. In this case, the positive electrode active material layer 100B may be heated, or the compression molding may be repeated multiple times.
[0094] As a result, the positive electrode active material layer 100B is formed on one surface of the positive electrode current collector 100A, and the positive electrode 100 is completed.
[0095] <1-4. Actions and Effects> According to this positive electrode 100, the positive electrode active material layer 100B contains a positive electrode active material and a positive electrode binder, the positive electrode active material contains an olivine-type phosphate compound, the positive electrode binder contains a water-soluble polymer compound and an oil-soluble polymer compound, the content of the water-soluble polymer compound in the positive electrode active material layer 100B is 1% by weight to 2% by weight, and the content of the oil-soluble polymer compound in the positive electrode active material layer 100B is 2% by weight to 6% by weight. Details of the water-soluble polymer compound and the oil-soluble polymer compound are as described above.
[0096] This results in a series of actions as described above and as follows.
[0097] First, the positive electrode active material contains an olivine-type phosphate compound, which suppresses the release of oxygen from the positive electrode active material during the electrode reaction of the positive electrode 100. This allows lithium to be stably absorbed and released in the positive electrode active material layer 100B, and the electrode reaction proceeds stably.
[0098] Secondly, the positive electrode binder contains a water-soluble polymer compound, and the content of the water-soluble polymer compound in the positive electrode active material layer 100B is 1% by weight to 2% by weight. In this case, the positive electrode active material particles are easily bound to each other by using only a small amount of the positive electrode binder, and the positive electrode active material particles are supplied to the surface of the positive electrode current collector 100A in a uniformly dispersed state when the positive electrode mixture slurry is applied. This allows the positive electrode active material layer 100B to be stably formed, thereby improving the operational stability of the secondary battery including the positive electrode 100.
[0099] Thirdly, the positive electrode binder contains a fat-soluble polymer compound, and the content of the fat-soluble polymer compound in the positive electrode active material layer 100B is 2% by weight to 6% by weight. In this case, the flexibility of the positive electrode active material layer 100B is improved, and the adhesion of the positive electrode active material layer 100B to the positive electrode current collector 100A is also improved. This makes the positive electrode active material layer 100B less likely to crack and less likely to peel off from the positive electrode current collector 100A, thereby improving the physical durability of the positive electrode 100.
[0100] For these reasons, in a secondary battery equipped with the positive electrode 100, stable progress of the electrode reaction is ensured, while the physical durability of the positive electrode 100 is improved and the operational stability of the secondary battery is improved, thereby obtaining excellent battery characteristics.
[0101] In particular, when the content of the water-soluble polymer compound in the positive electrode active material layer 100B is 1% by weight to 1.5% by weight, the physical durability of the positive electrode 100 is further improved and the operational stability of the secondary battery is further improved, thereby obtaining a greater effect.
[0102] Furthermore, if the content of the fat-soluble polymer compound in the positive electrode active material layer 100B is 3% by weight to 5% by weight, the physical durability of the positive electrode 100 is further improved and the operational stability of the secondary battery is further improved, thereby obtaining a greater effect.
[0103] Furthermore, if the median diameter MD2 of the positive electrode active material particles, which are the secondary particles, is 5 μm to 15 μm, the secondary particles are more likely to come into contact with each other, and thus the electronic conductivity between the positive electrode active material particles is improved, resulting in a greater effect.
[0104] In this case, if the median diameter MD1 of the primary particles is 0.1 μm to 1 μm, the primary particles are more likely to come into contact with each other, and therefore the electronic conductivity between the primary particles is improved, resulting in even greater effects.
[0105] Furthermore, if the olivine-type phosphate compound contains one or both of iron and manganese as constituent elements, the release of oxygen from the olivine-type phosphate compound is sufficiently suppressed, thereby achieving a greater effect.
[0106] <2. Secondary battery> Next, a secondary battery to which the positive electrode 100 is applied according to an embodiment of the present technology will be described.
[0107] The secondary battery described here is a secondary battery that obtains battery capacity by utilizing the absorption and release of an electrode reactant, and includes a positive electrode, a negative electrode, and an electrolyte. In the following, as described above, the electrode reactant is lithium. The secondary battery that obtains battery capacity by utilizing the absorption and release of lithium is a so-called lithium ion secondary battery. In this lithium ion secondary battery, lithium is absorbed and released in an ionic state.
[0108] The charge capacity of the negative electrode is preferably larger than the discharge capacity of the positive electrode. That is, the electrochemical capacity per unit area of the negative electrode is preferably larger than the electrochemical capacity per unit area of the positive electrode. This is to prevent lithium from being deposited on the surface of the negative electrode during charging.
[0109] <2-1. Configuration> FIG. 2 shows a cross-sectional configuration of a secondary battery which is an example of a secondary battery according to an embodiment of the present technology, and FIG. 3 shows a cross-sectional configuration of a battery element 20 shown in FIG.
[0110] 2 and 3, this secondary battery includes a battery can 11, a pair of insulating plates 12, 13, a battery element 20, a positive electrode lead 25, and a negative electrode lead 26. The secondary battery described here is a cylindrical secondary battery in which the battery element 20 is housed in the cylindrical battery can 11.
[0111] [Battery can] The battery can 11 is a member that houses the battery element 20 and the like. The battery can 11 has one open end and the other closed end, and thus has a hollow structure. The battery can 11 contains one or more types of metal materials such as iron, aluminum, iron alloys, and aluminum alloys. The surface of the battery can 11 may be plated with a metal material such as nickel.
[0112] At one open end of the battery can 11, a battery lid 14, a safety valve mechanism 15, and a PTC element 16, which is a thermal resistor element, are crimped via a gasket 17. Thus, the battery can 11 is sealed by the battery lid 14. Here, the battery lid 14 contains the same material as the material from which the battery can 11 is formed. The safety valve mechanism 15 and the PTC element 16 are provided inside the battery lid 14, and the safety valve mechanism 15 is electrically connected to the battery lid 14 via the PTC element 16. The gasket 17 contains an insulating material, and the surface of the gasket 17 may be coated with asphalt or the like.
[0113] In the safety valve mechanism 15, when the internal pressure of the battery can 11 reaches a certain level due to factors such as an internal short circuit or external heating, the disk plate 15A is inverted, cutting off the electrical connection between the battery cover 14 and the battery element 20. To prevent abnormal heat generation due to a large current, the electrical resistance of the PTC element 16 increases with increasing temperature.
[0114] [Insulating plate] The insulating plates 12 and 13 are disposed to face each other with the battery element 20 interposed therebetween. As a result, the battery element 20 is sandwiched between the insulating plates 12 and 13.
[0115] [Battery element] The battery element 20 is a so-called power generating element, and includes a positive electrode 21, a negative electrode 22, a separator 23, and an electrolyte (not shown).
[0116] This battery element 20 is a so-called wound electrode body, and therefore the positive electrode 21 and the negative electrode 22 are wound while facing each other with a separator 23 interposed therebetween. A center pin 24 is inserted into a space 20S provided at the winding center of the battery element 20. However, the center pin 24 may be omitted.
[0117] (positive electrode) The positive electrode 21 has a configuration similar to that of the positive electrode 100 .
[0118] Specifically, the positive electrode 21 includes a positive electrode current collector 21A and a positive electrode active material layer 21B. The configuration of the positive electrode current collector 21A is similar to that of the positive electrode current collector 100A, and the configuration of the positive electrode active material layer 21B is similar to that of the positive electrode active material layer 100B. Here, the positive electrode active material layer 21B is provided on both sides of the positive electrode current collector 21A. However, the positive electrode active material layer 21B may be provided only on one side of the positive electrode current collector 21A on the side where the positive electrode 21 faces the negative electrode 22.
[0119] (Negative electrode) The negative electrode 22 includes a negative electrode current collector 22A and a negative electrode active material layer 22B.
[0120] The negative electrode current collector 22A has a pair of surfaces on which the negative electrode active material layer 22B is provided. The negative electrode current collector 22A contains a conductive material such as a metal material, and a specific example of the conductive material is copper.
[0121] The negative electrode active material layer 22B includes one or more types of negative electrode active materials that absorb and release lithium. However, the negative electrode active material layer 22B may further include one or more types of other materials such as a negative electrode binder and a negative electrode conductive agent. The method for forming the negative electrode active material layer 22B is not particularly limited, and specifically includes one or more types of a coating method, a gas phase method, a liquid phase method, a thermal spraying method, and a baking method (sintering method).
[0122] Here, the negative electrode active material layer 22B is provided on both sides of the negative electrode current collector 22A. However, the negative electrode active material layer 22B may be provided on only one side of the negative electrode current collector 22A on the side where the negative electrode 22 faces the positive electrode 21.
[0123] The type of the negative electrode active material is not particularly limited, but specifically includes carbon materials and metal-based materials, etc., because a high energy density can be obtained.
[0124] Specific examples of the carbon material include graphitizable carbon, non-graphitizable carbon, graphite, etc. The graphite may be natural graphite or artificial graphite.
[0125] A metallic material is a material that contains, as a constituent element, one or more of metallic elements and semi-metallic elements that can form an alloy with lithium. Specific examples of metallic elements and semi-metallic elements include silicon and tin. This metallic material may be a simple substance, an alloy, a compound, a mixture of two or more of these, or a material containing two or more of these phases. However, since the simple substance may contain any amount of impurities, the purity of the simple substance is not necessarily limited to 100%. Specific examples of metallic materials include TiSi 2 and SiO x (0 <x≦2または0.2<x<1.4)などである。
[0126] The negative electrode binder contains one or more of materials such as synthetic rubber and polymer compounds. Specific examples of synthetic rubber include styrene-butadiene rubber, fluorine-based rubber, and ethylene-propylene-diene. Specific examples of polymer compounds include polyvinylidene fluoride, polyimide, and carboxymethyl cellulose.
[0127] The negative electrode conductive agent contains one or more conductive materials such as a carbon material, a metal material, and a conductive polymer compound. Specific examples of the carbon material include graphite, carbon black, acetylene black, and ketjen black.
[0128] (Separator) The separator 23 is an insulating porous film interposed between the positive electrode 21 and the negative electrode 22, and allows lithium to pass through in an ion state while preventing a short circuit caused by contact between the positive electrode 21 and the negative electrode 22. The separator 23 contains a polymer compound such as polyethylene.
[0129] (electrolyte) The electrolytic solution is a liquid electrolyte, and is impregnated into each of the positive electrode 21, the negative electrode 22, and the separator 23. The electrolytic solution contains a solvent and an electrolyte salt.
[0130] The solvent contains one or more types of non-aqueous solvents (organic solvents), and the electrolyte containing the non-aqueous solvent is a so-called non-aqueous electrolyte.
[0131] The non-aqueous solvent is an ester or an ether, more specifically, a carbonate compound, a carboxylate compound, a lactone compound, etc. This is because the dissociation property of the electrolyte salt and the mobility of the ions are improved.
[0132] The carbonate ester compounds are cyclic carbonate esters and chain carbonate esters. Specific examples of the cyclic carbonate esters are ethylene carbonate and propylene carbonate, and specific examples of the chain carbonate esters are dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate.
[0133] The carboxylate compound is a chain carboxylate, etc. Specific examples of the chain carboxylate are ethyl acetate, ethyl propionate, propyl propionate, and ethyl trimethylacetate.
[0134] The lactone compound is lactone, etc. Specific examples of lactone are γ-butyrolactone and γ-valerolactone, etc.
[0135] The ethers may be 1,2-dimethoxyethane, tetrahydrofuran, 1,3-dioxolane, 1,4-dioxane, or the like.
[0136] The non-aqueous solvent is, for example, an unsaturated cyclic carbonate, a fluorinated cyclic carbonate, a sulfonate, a phosphate, an acid anhydride, a nitrile compound, or an isocyanate compound, because the electrochemical stability of the electrolyte is improved.
[0137] Specific examples of unsaturated cyclic carbonates include vinylene carbonate, vinylethylene carbonate, and methyleneethylene carbonate. Specific examples of fluorinated cyclic carbonates include monofluoroethylene carbonate and difluoroethylene carbonate. Specific examples of sulfonic acid esters include propane sultone and propene sultone. Specific examples of phosphate esters include trimethyl phosphate and triethyl phosphate. Specific examples of acid anhydrides include succinic anhydride, 1,2-ethanedisulfonic anhydride, and 2-sulfobenzoic anhydride. Specific examples of nitrile compounds include succinonitrile. Specific examples of isocyanate compounds include hexamethylene diisocyanate.
[0138] The electrolyte salt contains one or more kinds of light metal salts such as lithium salts.
[0139] A specific example of a lithium salt is lithium hexafluorophosphate (LiPF 6 ), lithium tetrafluoroborate (LiBF 4 ), lithium trifluoromethanesulfonate (LiCF 3 SO 3 ), lithium bis(fluorosulfonyl)imide (LiN(FSO 2 ) 2 ), lithium bis(trifluoromethanesulfonyl)imide (LiN(CF 3 SO 2 ) 2 ), lithium tris(trifluoromethanesulfonyl)methide (LiC(CF 3 SO 2 ) 3 ), lithium bis(oxalato)borate (LiB(C 2 O 4 ) 2 ), lithium monofluorophosphate (Li 2 PFO 3 ) and lithium difluorophosphate (LiPF 2 O 2 ) This is because it allows for high battery capacity.
[0140] The content of the electrolyte salt is not particularly limited, but specifically, it is 0.3 mol / kg to 3.0 mol / kg relative to the solvent, because high ionic conductivity can be obtained.
[0141] [Positive and negative leads] The positive electrode lead 25 is connected to the positive electrode current collector 21A and contains a conductive material such as aluminum. The positive electrode lead 25 is electrically connected to the battery lid 14 via the safety valve mechanism 15.
[0142] The negative electrode lead 26 is connected to the negative electrode current collector 22A and contains a conductive material such as nickel. The negative electrode lead 26 is electrically connected to the battery can 11.
[0143] <2-2. Operation> A secondary battery operates as follows when charging and discharging.
[0144] During charging, in the battery element 20, lithium is released from the positive electrode 21 and is absorbed in the negative electrode 22 via the electrolyte. During discharging, in the battery element 20, lithium is released from the negative electrode 22 and is absorbed in the positive electrode 21 via the electrolyte. During charging and discharging, lithium is absorbed and released in an ionic state.
[0145] <2-3. Manufacturing method> When manufacturing a secondary battery, the positive electrode 21 and the negative electrode 22 are fabricated and the electrolyte is prepared using the procedure described below as an example, and then the secondary battery is assembled and subjected to a stabilization process after assembly.
[0146] [Preparation of positive electrode] The positive electrode 21 is produced by forming the positive electrode active material layers 21B on both sides of the positive electrode current collector 21A using a procedure similar to that for producing the positive electrode 100 described above.
[0147] [Preparation of negative electrode] First, a mixture (negative electrode mixture) in which the negative electrode active material, the negative electrode binder, and the negative electrode conductive agent are mixed together is poured into a solvent to prepare a paste-like negative electrode mixture slurry. This solvent may be an aqueous solvent or an organic solvent. Next, the negative electrode mixture slurry is applied to both sides of the negative electrode current collector 22A to form the negative electrode active material layer 22B. Finally, the negative electrode active material layer 22B may be compression molded using a compression device such as a roll press. In this case, the negative electrode active material layer 22B may be heated, or the compression molding may be repeated multiple times. As a result, the negative electrode active material layer 22B is formed on both sides of the negative electrode current collector 22A, and the negative electrode 22 is produced.
[0148] [Preparation of electrolyte] An electrolyte salt is added to a solvent, whereby the electrolyte salt is dispersed or dissolved in the solvent, and an electrolyte solution is prepared.
[0149] [Secondary battery assembly] First, the positive electrode lead 25 is connected to the positive electrode current collector 21A of the positive electrode 21 using a joining method such as welding, and the negative electrode lead 26 is connected to the negative electrode current collector 22A of the negative electrode 22 using a joining method such as welding.
[0150] Next, the positive electrode 21 and the negative electrode 22 are stacked on top of each other with the separator 23 interposed therebetween, and then the positive electrode 21, the negative electrode 22, and the separator 23 are wound to produce a wound body (not shown) having a space 20S. This wound body has a configuration similar to that of the battery element 20, except that the positive electrode 21, the negative electrode 22, and the separator 23 are not impregnated with an electrolyte. Next, a center pin 24 is inserted into the space 20S of the wound body.
[0151] Next, with the wound body sandwiched between the insulating plates 12 and 13, the wound body and the insulating plates 12 and 13 are housed in the battery can 11. In this case, the positive electrode lead 25 is connected to the safety valve mechanism 15 using a joining method such as welding, and the negative electrode lead 26 is connected to the battery can 11 using a joining method such as welding. Next, an electrolyte is injected into the battery can 11, so that the wound body is impregnated with the electrolyte. As a result, the positive electrode 21, the negative electrode 22, and the separator 23 are each impregnated with the electrolyte, and the battery element 20 is produced.
[0152] Finally, the battery cover 14 , the safety valve mechanism 15 and the PTC element 16 are housed in the battery can 11 , and then the battery can 11 is crimped via the gasket 17 .
[0153] As a result, the battery lid 14, the safety valve mechanism 15 and the PTC element 16 are fixed to the battery can 11, and the battery element 20 is sealed in the battery can 11, thereby assembling a secondary battery.
[0154] [Stabilization of secondary batteries after assembly] The assembled secondary battery is charged and discharged. The charging and discharging conditions, such as the environmental temperature, the number of charging and discharging times (number of cycles), and the charging and discharging conditions, can be set arbitrarily. As a result, a coating is formed on the surface of each of the positive electrode 21 and the negative electrode 22, so that the state of the battery element 20 is electrochemically stabilized. Thus, the secondary battery is completed.
[0155] <2-4. Actions and Effects> In this secondary battery, the positive electrode 21 has a configuration similar to that of the positive electrode 100. Therefore, for the reasons described above, the physical durability of the positive electrode 21 is improved and the operational stability of the secondary battery is improved, so that excellent battery characteristics can be obtained.
[0156] In particular, if the secondary battery is a lithium ion secondary battery, a sufficient battery capacity can be stably obtained by utilizing the absorption and release of lithium, so that a greater effect can be obtained.
[0157] Other functions and effects of the secondary battery are similar to those of the positive electrode 100.
[0158] <3. Modifications> The configuration of the secondary battery described above can be modified as appropriate, as described below, although the series of modifications described below may be combined with each other.
[0159] [Variation 1] A porous membrane separator 23 was used. However, although not specifically shown here, a laminated separator may also be used.
[0160] Specifically, the laminated separator includes a porous film and a polymer compound layer. The porous film has a pair of surfaces, and the polymer compound layer is provided on one or both surfaces of the porous film. This is because the adhesion of the separator to the positive electrode 21 and the negative electrode 22 is improved, and thus the winding deviation of the positive electrode 21, the negative electrode 22, and the separator 23 is suppressed. This suppresses swelling of the secondary battery even if a decomposition reaction of the electrolyte occurs. The polymer compound layer includes a polymer compound such as polyvinylidene fluoride. This is because polyvinylidene fluoride has excellent physical strength and is electrochemically stable.
[0161] One or both of the porous film and the polymer compound layer may contain a plurality of insulating particles. This is because the plurality of insulating particles promotes heat dissipation when the secondary battery generates heat, thereby improving the safety (heat resistance) of the secondary battery. The plurality of insulating particles contain one or more types of insulating materials such as inorganic materials and resin materials. Specific examples of inorganic materials include aluminum oxide, aluminum nitride, boehmite, silicon oxide, titanium oxide, magnesium oxide, and zirconium oxide. Specific examples of resin materials include acrylic resin and styrene resin.
[0162] In the case of producing a laminated separator, a precursor solution containing a polymer compound and a solvent is prepared, and then the precursor solution is applied to one or both sides of a porous film. In this case, a plurality of insulating particles may be added to the precursor solution as necessary.
[0163] Even when this laminated separator is used, the same effect can be obtained because lithium becomes movable between the positive electrode 21 and the negative electrode 22. In this case, as described above, the safety of the secondary battery is particularly improved, and therefore, a higher effect can be obtained.
[0164] [Variation 2] An electrolyte solution that is a liquid electrolyte is used, but an electrolyte layer that is a gel electrolyte may also be used, although this is not specifically shown.
[0165] In the battery element 20 using the electrolyte layer, the positive electrode 21 and the negative electrode 22 are wound facing each other with the separator 23 and the electrolyte layer interposed therebetween. The electrolyte layer is interposed between the positive electrode 21 and the separator 23, and is also interposed between the negative electrode 22 and the separator 23.
[0166] Specifically, the electrolyte layer contains a polymer compound together with an electrolyte solution, and the electrolyte solution is held by the polymer compound. This is because leakage of the electrolyte solution is prevented. The composition of the electrolyte solution is as described above. The polymer compound contains polyvinylidene fluoride and the like. When forming the electrolyte layer, a precursor solution containing an electrolyte solution, a polymer compound, and a solvent is prepared, and then the precursor solution is applied to one or both sides of each of the positive electrode 21 and the negative electrode 22.
[0167] Even when this electrolyte layer is used, the same effect can be obtained because lithium can move between the positive electrode 21 and the negative electrode 22 via the electrolyte layer. In this case, leakage of the electrolyte is particularly prevented as described above, so that a higher effect can be obtained.
[0168] <4. Uses of secondary batteries> The use (application example) of the secondary battery is not particularly limited. The secondary battery used as a power source may be a main power source or an auxiliary power source in electronic devices, electric vehicles, etc. The main power source is a power source that is used preferentially regardless of the presence or absence of other power sources. The auxiliary power source may be a power source used in place of the main power source, or a power source that is switched from the main power source.
[0169] Specific examples of uses of secondary batteries are as follows: Electronic devices such as video cameras, digital still cameras, mobile phones, notebook computers, headphone stereos, portable radios, and portable information terminals. Storage devices such as backup power sources and memory cards. Power tools such as power drills and power saws. Battery packs mounted on electronic devices. Medical electronic devices such as pacemakers and hearing aids. Electric vehicles such as electric cars (including hybrid cars). Power storage systems such as home or industrial battery systems that store power in preparation for emergencies. In these uses, one secondary battery may be used, or multiple secondary batteries may be used.
[0170] The battery pack may use a single cell or a battery pack. The electric vehicle is a vehicle that runs on a secondary battery as a driving power source, and may be a hybrid vehicle that also includes a driving source other than the secondary battery. In the home power storage system, it is possible to use home electrical appliances and the like by utilizing the power stored in the secondary battery, which is a power storage source. EXAMPLES
[0171] An embodiment of the present technology will be described.
[0172] <Examples 1 to 33 and Comparative Examples 1 to 13> As described below, after the secondary batteries were manufactured, the battery characteristics of the secondary batteries were evaluated.
[0173] [Secondary battery manufacturing] Here, in order to simply evaluate the battery characteristics, a test secondary battery was fabricated as described below. In the following, the configuration of the test secondary battery will be described, and then the fabrication procedure of the test secondary battery will be described.
[0174] (Structure of secondary battery) 4 shows a cross-sectional structure of a test secondary battery, which is a so-called coin-type lithium-ion secondary battery. Hereinafter, the test secondary battery will also be referred to simply as a "secondary battery."
[0175] As shown in FIG. 4, this secondary battery includes a test electrode 61, a counter electrode 62, a separator 63, an exterior cup 64, an exterior can 65, a gasket 66, and an electrolyte (not shown).
[0176] The test electrode 61 is housed in an exterior cup 64, and the counter electrode 62 is housed in an exterior can 65. The test electrode 61 and the counter electrode 62 are stacked together with a separator 63 interposed therebetween, and the test electrode 61, the counter electrode 62, and the separator 63 are each impregnated with an electrolyte. The exterior cup 64 and the exterior can 65 are crimped together with a gasket 66, so that the test electrode 61, the counter electrode 62, and the separator 63 are sealed by the exterior cup 64 and the exterior can 65.
[0177] (Secondary battery manufacturing procedure) The secondary battery shown in FIG. 5 was fabricated using the procedure described below.
[0178] (Preparation of test pole) When preparing the test electrode 61, first, a plurality of positive electrode active material particles (LiFePO 4 The positive electrode active material particles were aggregates (secondary particles) of multiple primary particles, and the median diameters MD1 and MD2 (μm) were measured after the secondary battery was completed. The results are shown in Tables 1 to 4.
[0179] Next, 100 parts by mass of the positive electrode active material particles (LFP), 5 parts by mass of the emulsion solution, 2 parts by mass of the positive electrode conductive agent (graphite), and 20 parts by mass of a solvent for adjusting viscosity (pure water, which is an aqueous solvent) were mixed together to prepare a positive electrode mixture slurry. This emulsion solution contains an aqueous solvent (pure water), a water-soluble polymer compound (lithium acrylate-acrylonitrile-acrylamide copolymer (COP1)), and an oil-soluble polymer compound (acrylonitrile-methyl acrylate-methyl methacrylate copolymer (COP2)).
[0180] After the secondary battery was completed, the content (wt %) of the water-soluble polymer compound in the positive electrode active material layer and the content (wt %) of the fat-soluble polymer compound in the positive electrode active material layer were examined. The results are shown in Tables 1 to 4.
[0181] Next, the positive electrode mixture slurry was applied to one side of a positive electrode current collector (aluminum foil, thickness = 12 μm) using a coating device, and then the positive electrode mixture slurry was dried to form a positive electrode active material layer. In this case, the amount of the positive electrode mixture slurry applied was 15 mg / cm. 2 It was decided.
[0182] Next, the positive electrode active material layer was compression molded using a press. In this case, the volume density of the positive electrode active material layer was 2.1 g / cm 3 It was decided.
[0183] Finally, the positive electrode current collector on which the positive electrode active material layer was formed was punched out into a disk shape (diameter = 16.5 mm), thereby producing a test electrode 61.
[0184] (Preparation of counter electrode) The lithium metal plate was punched out into a disk shape (diameter = 17 mm), thereby obtaining the counter electrode 62.
[0185] (Preparation of electrolyte) Solvent (cyclic carbonate ethylene carbonate and chain carbonate diethyl carbonate) is mixed with electrolyte salt (LiPF 6) was added, and the solvent was stirred. In this case, the mixing ratio (weight ratio) of the solvent was ethylene carbonate:diethyl carbonate=30:70, and the content of the electrolyte salt in the electrolyte was 1 mol / kg relative to the solvent. Thus, the electrolyte was prepared.
[0186] (Secondary battery assembly) First, the test electrode 61 was accommodated in an exterior cup 64, and the counter electrode 62 was accommodated in an exterior can 65. Next, the test electrode 61 accommodated in the exterior cup 64 and the counter electrode 62 accommodated in the exterior can 65 were laminated together via a separator 63 (microporous polyethylene film, thickness = 20 μm, diameter = 17.5 mm) impregnated with an electrolyte. In this case, the positive electrode active material layer and the counter electrode 62 were made to face each other via the separator 63.
[0187] Next, in a state in which the test electrode 61 and the counter electrode 62 were stacked together with the separator 63 interposed therebetween, the exterior cup 64 and the exterior can 65 were crimped together via the gasket 66. As a result, the test electrode 61 and the counter electrode 62 were sealed by the exterior cup 64 and the exterior can 65, and a secondary battery was assembled.
[0188] Finally, the assembled secondary battery was left to stand (standing time = 10 hours), thereby completing the secondary battery.
[0189] [Evaluation of battery characteristics] When the physical durability and operational stability were evaluated as the battery characteristics, the results shown in Tables 1 to 4 were obtained. Here, using the procedure described below, the adhesion and flexibility of the test electrode 61 were evaluated as the physical durability, and the load characteristics and cycle characteristics of the secondary battery were evaluated as the operational stability.
[0190] (Adhesion) First, the secondary battery was disassembled to recover the test electrode 61. Next, the test electrode 61 was washed with a washing solvent (pure water), and then the test electrode 61 was dried.
[0191] Next, the test electrode 61 was attached to a peel tester in a room temperature environment (temperature = 23 ° C.), and then a 180 ° peel test was performed using the peel tester. As a result, the positive electrode current collector was peeled off from the positive electrode active material layer, and the peel strength (mN / mm), which is an index for evaluating adhesion, was measured.
[0192] Finally, the adhesion was judged based on the peel strength. Specifically, when the peel strength was 20 mN / mm or more, it was judged as "A." When the peel strength was less than 20 mN / mm, it was judged as "C."
[0193] (Flexibility) First, the test electrode 61 was collected from the secondary battery using the same procedure as in the case of evaluating the adhesion, and then the test electrode 61 was washed.
[0194] Next, the test electrode 61 was curved by wrapping the test electrode 61 around the surface of an iron metal rod (diameter = 4 mm) in a room temperature environment, and the test electrode 61 in the curved state was left (leaving time = 10 minutes). Next, the state of the test electrode 61 was visually confirmed to observe the state of the positive electrode active material layer, which is an index for evaluating flexibility.
[0195] Finally, flexibility was judged based on the state of the positive electrode active material layer. Specifically, when no abnormality occurred in the positive electrode active material layer, it was judged as "A". When an abnormality occurred in the positive electrode active material layer, it was judged as "C". The abnormalities in the positive electrode active material layer described here include cracks, breakage, and falling off.
[0196] (Load characteristics) First, the secondary battery was charged and discharged one cycle in a room temperature environment to measure the discharge capacity (discharge capacity in the first cycle).
[0197] During charging, the battery was charged at a constant current of 0.2 C until the voltage reached 3.8 V, and then was charged at a constant voltage of 3.8 V until the current reached 0.05 C. During discharging, the battery was discharged at a constant current of 0.2 C until the voltage reached 2.0 V. 0.2 C is the current value at which the battery capacity (theoretical capacity) is fully discharged in 5 hours, and 0.05 C is the current value at which the battery capacity is fully discharged in 20 hours.
[0198] Next, the secondary battery was charged and discharged for one cycle in the same environment to measure the discharge capacity (discharge capacity at the second cycle).
[0199] The charge and discharge conditions were the same as those of the first cycle, except that the discharge current was changed from 0.2 C to 2 C. 2 C is the current value at which the battery capacity is fully discharged in 0.5 hours.
[0200] Next, the load retention rate, which is an index for evaluating the load characteristics, was calculated based on the formula: Load retention rate (%)=(Discharge capacity at 2nd cycle / Discharge capacity at 1st cycle)×100.
[0201] Finally, the load characteristics were judged based on the load maintenance rate. Specifically, when the load maintenance rate was 90% or more, it was judged as "A". When the load maintenance rate was 80% or more and less than 90%, it was judged as "B". When the load maintenance rate was less than 80%, it was judged as "C".
[0202] (Cycle characteristics) First, the secondary battery was charged and discharged one cycle in a room temperature environment to measure the discharge capacity (discharge capacity at the first cycle). Next, the secondary battery was repeatedly charged and discharged in the same environment until the total number of cycles reached 100 cycles, to measure the discharge capacity (discharge capacity at the 100th cycle). The charge and discharge conditions were the same as those for the first cycle when the load characteristics were evaluated.
[0203] Next, the cycle retention rate, which is an index for evaluating cycle characteristics, was calculated based on the formula: cycle retention rate (%)=(discharge capacity at 100th cycle / discharge capacity at 1st cycle)×100.
[0204] Finally, the cycle characteristics were evaluated based on the cycle retention rate. Specifically, when the cycle retention rate was 90% or more, it was evaluated as "A." When the cycle retention rate was less than 90%, it was evaluated as "C."
[0205] (comprehensive evaluation) Here, the adhesion and flexibility were evaluated, and the load characteristics and cycle characteristics were evaluated, and then the battery characteristics were evaluated comprehensively based on the evaluation results.
[0206] Specifically, if any one of the four types of judgment results regarding adhesion, flexibility, load characteristics, and cycle characteristics was judged to be C, the overall evaluation was rated as "C." If none of the four types of judgment results was judged to be C and the judgment result regarding the load characteristics was B, the overall evaluation was rated as "B." If none of the four types of judgment results was judged to be C and the judgment result regarding the load characteristics was A, the overall evaluation was rated as "A."
[0207] [Table 1]
[0208] [Table 2]
[0209] [Table 3]
[0210] [Table 4]
[0211] [Consideration] As shown in Tables 1 to 4, when the test electrode 61 contained an olivine-type phosphate compound as a positive electrode active material, the overall evaluation of the four evaluation results (adhesion, flexibility, load characteristics, and cycle characteristics) varied depending on the configuration of the test electrode 61.
[0212] Specifically, when the positive electrode binder contained a water-soluble polymer compound and an oil-soluble polymer compound, and the content of the water-soluble polymer compound in the positive electrode active material layer was 1 wt % to 2 wt %, and the content of the oil-soluble polymer compound in the positive electrode active material layer was 2 wt % to 6 wt %, the appropriate conditions were not met (Comparative Examples 1 to 13), and any one of the adhesion, flexibility, load characteristics, and cycle characteristics was deteriorated, so the overall evaluation was C.
[0213] In contrast, when the above-mentioned appropriate conditions were met (Examples 1 to 33), the adhesion, flexibility, load characteristics and cycle characteristics were all improved, and the overall evaluation was B or higher.
[0214] In particular, when the appropriate conditions were met (Examples 1-33), a series of trends were obtained, as explained below.
[0215] First, when the water-soluble polymer compound contained lithium acrylate-acrylonitrile-acrylamide copolymer and the fat-soluble polymer compound contained acrylonitrile-methyl acrylate-methyl methacrylate copolymer, the flexibility, load characteristics and cycle characteristics were all sufficiently improved.
[0216] Secondly, when the content of the water-soluble polymer compound in the positive electrode active material layer was 1% by weight to 1.5% by weight, the load characteristics were further improved.
[0217] Thirdly, when the content of the fat-soluble polymer compound in the positive electrode active material layer was 3% by weight to 5% by weight, the load characteristics were further improved.
[0218] Fourth, when the median diameter MD2 was 5 μm to 15 μm, the load characteristics were further improved.
[0219] Fifth, when the median diameter MD1 was 0.1 μm to 1 μm, the adhesion, load characteristics, and cycle characteristics were all further improved.
[0220] Sixth, when the olivine-type phosphate compound contains iron as a constituent element, the flexibility, load characteristics, and cycle characteristics are all significantly improved. This tendency should be similarly obtained when the olivine-type phosphate compound contains manganese as a constituent element instead of iron.
[0221] [summary] From the results shown in Tables 1 to 4, when the positive electrode active material layer contains a positive electrode active material and a positive electrode binder, the positive electrode active material contains an olivine-type phosphate compound, the positive electrode binder contains a water-soluble polymer compound and an oil-soluble polymer compound, the content of the water-soluble polymer compound in the positive electrode active material layer is 1% by weight to 2% by weight, and the content of the oil-soluble polymer compound in the positive electrode active material layer is 2% by weight to 6% by weight, the adhesion, flexibility, load characteristics, and cycle characteristics are all improved. Therefore, the physical durability of the test electrode 61 was improved, and the operating stability of the secondary battery equipped with the test electrode 61 was also improved, so that excellent battery characteristics were obtained.
[0222] Although the present technology has been described above with reference to an embodiment and examples, the configuration of the present technology is not limited to the configuration described in the embodiment and examples and can be modified in various ways.
[0223] Specifically, the battery structure of the secondary battery has been described as being cylindrical and coin-shaped. However, the battery structure of the secondary battery is not particularly limited, and may be a laminate film type, a square type, a button type, or the like.
[0224] Also, the battery element has been described as having a wound structure. However, the structure of the battery element is not particularly limited, and may be a stacked structure or a zigzag structure. In the stacked structure, the positive and negative electrodes are stacked on top of each other, and in the zigzag structure, the positive and negative electrodes are folded in a zigzag pattern.
[0225] Furthermore, although the electrode reactant is lithium, the electrode reactant is not particularly limited. Specifically, the electrode reactant may be other alkali metals such as sodium and potassium, as described above, or alkaline earth metals such as beryllium, magnesium, and calcium. In addition, the electrode reactant may be other light metals such as aluminum.
[0226] The effects described in this specification are merely examples, and the effects of the present technology are not limited to the effects described in this specification. Therefore, other effects may be obtained with respect to the present technology.
[0227] The present technology can also be configured as follows. <1> a positive electrode including a positive electrode active material layer; A negative electrode; Electrolyte and Equipped with The positive electrode active material layer includes a positive electrode active material and a positive electrode binder, The positive electrode active material contains a phosphate compound having an olivine type crystal structure, The positive electrode binder contains a water-soluble polymer compound and an oil-soluble polymer compound, The water-soluble polymer compound contains at least one polymer selected from the group consisting of acrylates, acrylonitrile, and acrylamide, the fat-soluble polymer compound contains at least one polymer selected from the group consisting of acrylonitrile, acrylic acid esters, and methacrylic acid esters; The content of the water-soluble polymer compound in the positive electrode active material layer is 1% by weight or more and 2% by weight or less, The content of the fat-soluble polymer compound in the positive electrode active material layer is 2% by weight or more and 6% by weight or less. Secondary battery. <2> The content of the water-soluble polymer compound in the positive electrode active material layer is 1% by weight or more and 1.5% by weight or less. <1> The secondary battery according to claim 1. <3> The content of the fat-soluble polymer compound in the positive electrode active material layer is 3% by weight or more and 5% by weight or less. <1> or <2> The secondary battery according to claim 1. <4> The positive electrode active material includes a plurality of secondary particles, The median diameter of the secondary particles is 5 μm or more and 15 μm or less. <1> Or <3> 13. The secondary battery according to claim 12, <5> The secondary particles include a plurality of primary particles, The median diameter of the primary particles is 0.1 μm or more and 1 μm or less. <4> The secondary battery according to claim 1. <6> The phosphate compound contains one or both of iron and manganese as constituent elements. <1> Or <5> 13. The secondary battery according to claim 12, <7> It is a lithium-ion secondary battery. <1> Or <6> 13. The secondary battery according to claim 12, <8> A positive electrode active material layer is provided, The positive electrode active material layer includes a positive electrode active material and a positive electrode binder, The positive electrode active material contains a phosphate compound having an olivine type crystal structure, The positive electrode binder contains a water-soluble polymer compound and an oil-soluble polymer compound, The water-soluble polymer compound contains at least one polymer selected from the group consisting of acrylates, acrylonitrile, and acrylamide, the fat-soluble polymer compound contains at least one polymer selected from the group consisting of acrylonitrile, acrylic acid esters, and methacrylic acid esters; The content of the water-soluble polymer compound in the positive electrode active material layer is 1% by weight or more and 2% by weight or less, The content of the fat-soluble polymer compound in the positive electrode active material layer is 2% by weight or more and 6% by weight or less. Positive electrode for secondary batteries. [Explanation of symbols]
[0228] 20... battery element, 21,100... positive electrode, 21B,100B... positive electrode active material layer, 22... negative electrode.
Claims
1. a positive electrode including a positive electrode active material layer; A negative electrode; Electrolyte and Equipped with The positive electrode active material layer includes a positive electrode active material and a positive electrode binder, The positive electrode active material contains a phosphate compound having an olivine type crystal structure, The positive electrode binder contains a water-soluble polymer compound and an oil-soluble polymer compound, The water-soluble polymer compound includes at least one polymer selected from the group consisting of acrylates, acrylonitrile, and acrylamide; the fat-soluble polymer compound contains at least one polymer selected from the group consisting of acrylonitrile, acrylic acid esters, and methacrylic acid esters; the content of the water-soluble polymer compound in the positive electrode active material layer is 1% by weight or more and 2% by weight or less, The content of the fat-soluble polymer compound in the positive electrode active material layer is 2% by weight or more and 6% by weight or less. Secondary battery.
2. The content of the water-soluble polymer compound in the positive electrode active material layer is 1% by weight or more and 1.5% by weight or less. The secondary battery according to claim 1 .
3. The content of the fat-soluble polymer compound in the positive electrode active material layer is 3% by weight or more and 5% by weight or less. The secondary battery according to claim 1 .
4. The positive electrode active material includes a plurality of secondary particles, The median diameter of the multiple secondary particles is 5 μm or more and 15 μm or less. The secondary battery according to claim 1 .
5. The secondary particles include a plurality of primary particles, The median diameter of the plurality of primary particles is 0.1 μm or more and 1 μm or less. The secondary battery according to claim 4 .
6. The phosphate compound contains one or both of iron and manganese as constituent elements. The secondary battery according to claim 1 .
7. It is a lithium-ion secondary battery. The secondary battery according to claim 1 .
8. A positive electrode active material layer is provided, The positive electrode active material layer includes a positive electrode active material and a positive electrode binder, The positive electrode active material contains a phosphate compound having an olivine type crystal structure, The positive electrode binder contains a water-soluble polymer compound and an oil-soluble polymer compound, The water-soluble polymer compound includes at least one polymer selected from the group consisting of acrylates, acrylonitrile, and acrylamide; the fat-soluble polymer compound contains at least one polymer selected from the group consisting of acrylonitrile, acrylic acid esters, and methacrylic acid esters; the content of the water-soluble polymer compound in the positive electrode active material layer is 1% by weight or more and 2% by weight or less, The content of the fat-soluble polymer compound in the positive electrode active material layer is 2% by weight or more and 6% by weight or less. Positive electrode for secondary batteries.
Citation Information
Patent Citations
Lithium-ion secondary battery
WO2011122297A1
Lithium ion secondary battery cathode and lithium ion secondary battery
WO2014112436A1
Positive electrode for nonaqueous electrolyte battery and battery using positive electrode
JP2005251554A
Positive electrode for lithium secondary battery, and lithium secondary battery
JP2010272272A